Utilization of fish silos in the semi-humid diet formulation for red tilapias (Oreochromis niloticus x O. mossambicus) - Llanes, J.; Toledo, J.; Sav?n, Lourdes; Guti?rrez, Odilia (Cuban Journal of Agricultural Science, 2012)
The effect of two semi-humid diets, formulated with silages (chemical and biological) from red tilapia slicing residues, as only animal protein source, was assessed on the feeding of red tilapias (Oreochromis niloticus x O. mossambicus). Thus, one-way classification models were applied with three repetitions. The physical stability of the diets was determined by dry matter loss and protein lixiviation after water immersion. The in vivo digestibility was calculated by the indirect method with chromium oxide III as inert marker. The feces collection was carried out using a siphon at the bottom of the tanks. The growth bioassay was conducted for 60 d, with 270 sex-reversed fingerlings (all-male) of 6.0 + 0.01 g of weight as initial average. Satisfactory losses of dry matter (11.4 and 10.9 %) and protein lixiviation (16.4 and 15.9 %) were found in the experimental rations, which differed from the control (5.1 and 4.7 %). The lowest protein digestibility was reported in the diet with biological silage (86.8 %), differing (P < 0.01) from the chemical (89.4 %) and the control (88.7 %). The productive performance showed that there were not significant differences in the final weights (30.0; 29.9 and 29.6 g), the feed conversion (1.5; 1.5 and 1.6) and protein efficiency (1.8; 1.9 and 1.8) in fish fed silages and fish meal. The survival was high for all the treatments (higher than 95 %). It was evidenced that the semi-humid diets, based on silages from tilapia slicing residues, are as efficient in the productive performance of red tilapias as the commercial feeds with fishmeal, which represents a feeding alternative for cultures of this species. Key words: feeding, alternative diets, fish silage, tilapia.